Neural anti-inflammatory sesquiterpenoids from the endophytic fungus Trichoderma sp. Xy24. Issue 7 (3rd July 2017) - Zhang, Min; Zhao, Jin-Lian; Liu, Ji-Mei; Chen, Ri-Dao; Xie, Ke-Bo; Chen, Da-Wei; Feng, Ke-Ping; Zhang, Dan; Dai, Jun-Gui
Abstract: Three new sesquiterpenoids trichoacorenols B–C and cyclonerodiol B (1 –3 ), along with three known ones (4 –6 ), were isolated from the mangrove plant endophytic fungus Trichoderma sp. Xy24 using various column chromatography techniques. The structures of these compounds were determined on the basis of extensive spectroscopic data analyses. Compounds1, 2, 4, and5 were four acorane sesquiterpenes, 3 and6 were two monocyclic sesquiterpenediols. Compounds3 and5 exhibited significant neural anti-inflammatory activity by inhibiting LPS-induced NO production in BV2 cells with the inhibitory rates of 75.0% and 39.2% at 0.1 μM, respectively, which are more potent than curcumin, a positive control with the inhibitory rate of 21.1% at 0.1 μM. Abstract :